The design of shading louvres for solar energy collection - Eissa, Khalid W. (2005)
Shading louvres on buildings must serve to allow maximum window insolation in winter, while have the prime function of intercepting unwanted direct solar radiation in summer; which could cause excessive solar heat gain, especially in glazed offices and commercial spaces. Studies of the effect of solar protection on heating and cooling loads show that shading strategies are climate dependent. And it is accepted today that solar protection does reduce energy use for cooling, and tends to increase heating loads. The balance between the benefits in cooling and the losses in heating is only achievable by good designs. The main focus of this research work has been in harnessing the thermal energy available within the incident solar radiation intercepted by the shading louvres; hence benefiting, from shading in terms of energy savings, as well as from the collected energy. In achieving this aim, both theoretical and experimental techniques have been utilized, as design analysis tools, in order to select a design that satisfies both the efficiency and cost criteria. A suitable collector design has, then, been identified, its thermal performance characterised, and its prototype manufactured and built. The prototype of the chosen design has been field-tested in Nottingham-England and Porto-Portugal. Finally, the characteristics of the design have been incorporated into a computer simulation scenario, in which a real office building in Winterthur-Switzerland has been analysed for its total (cooling and heating) annual energy consumption. Findings of this research work indicate that these louvres, despite certain geometrical limitations, could act as solar collectors with good energy collection characteristics. And they could contribute with substantial reductions in the overall annual energy consumption resulting from the combined effect of shading and collecting energy. This was found particularly to be the case when the collected energy is made to part-fuel, an adsorption chiller for the purpose of air-conditioning the same building. [Pages 204, 206-7, 211-16 not scanned.]